Selbstständigkeit im Handwerk unter besonderer Berücksichtigung der Betriebsnachfolge Steuerrechtliche Rahmenbedingungen und Erleichterungen de lege lata und de lege ferenda - Drüen, Klaus-Dieter (Wirtschaft und Recht für Mittelstand und Handwerk, 2021)
This work deals with the topic of supporting the foundation and transfer of craft enterprises. While the current tax law in Germany already provides incentives to facilitate the foundation and transfer of small and medium-sized enterprises in general (e.g. through investment deductions and special depreciation allowances) and for craft enterprises in particular (e.g. through tax reductions for craftsmen's services), there is further potential to promote self-employment and business succession under tax law. Against the background of an inter-periodic and European legal comparison, this study presents further ideas and concrete proposals on substantive tax law and tax implementation with the aim of making tax law even more founder- and takeover-friendly.